An Exploration of Mental Health Practitioners’ Experience of the COVID-19 Pandemic: Understanding the Physical, Psychological and Spiritual Implications - Osman, Leila (Université d'Ottawa | University of Ottawa, 2026)
The exploration of the mental health practitioners’ (MHP) ability to be present with clients’ emotions, uncertainties, questions, and discomforts is not a new line of investigation. However, within the context of COVID-19, this precise moment in time offers not only a new lens through which to explore some of these factors but also provides a unique opportunity to delve more deeply into questions of coping while under collective and ongoing trauma, as well as meaning-making in the field of mental healthcare. This research endeavoured to offer a new glimpse into understanding the implications of COVID-19 on the physical, psychological, and spiritual lives of MHPs, while exploring how MHPs have worked to care for their well-being while facing a myriad of personal and professional uncertainties. The goal of this research is to gain an understanding of how MHPs have experienced the pandemic (both personally and professionally), and to understand if and how meaning can be made or found in the midst of uncertainty, and ongoing, collective, and shared trauma. This research shone a light on gaps in the research, and the resources, for those in the helping and health professions in times of collective or personal challenge, which may prove fruitful as areas for future research, development, and application.
Keywords: Mental health practitioners; COVID-19; Crisis preparedness; Best practices